Holistika Pendidikan Perspektif Malik Fadjar dan Relefansinya terhadap Pendidikan Islam di Era Digitalisasi - Muhammad Ihsanuddin Fathoni; Alfi Taufik (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study explores Malik Fadjar’s concept of holistic education and its relevance to Islamic education in the digital era. As a reformist Muslim scholar, Malik Fadjar emphasizes that education must function as a comprehensive humanization process, integrating intellectual, spiritual, moral, social, and cultural dimensions. Through a library research method, this study examines primary sources from Malik Fadjar’s writings and speeches, alongside secondary literature discussing holistic education and digital transformation in educational contexts. The findings indicate that Malik Fadjar’s holistic framework rejects the fragmentation of knowledge and promotes an integrated paradigm that aligns religious values with contemporary demands. In the digital era, characterized by rapid technological change and information abundance, this holistic perspective remains essential. It offers a philosophical foundation for developing Islamic education that not only adopts digital tools but also strengthens character formation, digital literacy, and adaptive skills. Therefore, Malik Fadjar’s holistic educational thought provides a relevant and strategic contribution to shaping Islamic education models that are modern, competitive, and grounded in humanistic values